(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Despite the lack of a precise definition of "digital diplomacy," all global actors are currently attempting to establish e-diplomacy within their government structures, and each foreign policy agency and diplomatic mission is defining and experimenting with it individually. Internet diplomacy refers to the use of ICT and online platforms by international actors to define and clarify foreign policy intentions and priorities, as well as the productive implementation of missions by individuals representing the national interests of international actors. E-diplomacy is a fruitful method of foreign policy activity, as it interacts with public diplomacy, which utilizes ICT. Public diplomacy offers the opportunity to utilize online platforms, and thanks to users of online platforms, the chances of engaging people are increased, and their views are also prominent both within the state and internationally [1].